2013
DOI: 10.1128/iai.00150-13
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Immune Response Induced by Mycobacterium avium Complex Strains in a Model of Progressive Pulmonary Tuberculosis and Subcutaneous Infection in BALB/c Mice

Abstract: eThe genus Mycobacterium comprises more than 150 species, including important pathogens for humans which cause major public health problems. The vast majority of efforts to understand the genus have been addressed in studies with Mycobacterium tuberculosis. The biological differentiation between M. tuberculosis and nontuberculous mycobacteria (NTM) is important because there are distinctions in the sources of infection, treatments, and the course of disease. Likewise, the importance of studying NTM is not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…This is supported by the fact that an elevation in inflammatory markers such as C-reactive protein and erythrocyte sedimentation rate was significantly associated with MAC-LD progression, further impacting the degree of sputum conversion and MAC-specific mortality [7,9,20]. It has been found that many pro-or anti-inflammatory cytokines are activated to varying degrees in severe, advanced MAC infection [21][22][23].…”
Section: Discussionmentioning
confidence: 93%
“…This is supported by the fact that an elevation in inflammatory markers such as C-reactive protein and erythrocyte sedimentation rate was significantly associated with MAC-LD progression, further impacting the degree of sputum conversion and MAC-specific mortality [7,9,20]. It has been found that many pro-or anti-inflammatory cytokines are activated to varying degrees in severe, advanced MAC infection [21][22][23].…”
Section: Discussionmentioning
confidence: 93%
“…To determine whether selection of My‐HSCs by IFNγ signaling occurs during infection in vivo, we utilized M. avium infection to elicit an IFNγ‐mediated immune response in mice . Notably, the M. avium ‐infected animals showed a specific depletion in the proportion and total number of HSCs in the lower part of the SP distribution, characteristic of myeloid‐biased HSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Humans are exposed to Mycobacterium from domestic animals through contami-nated foodstuffs or by direct contact with the animals and their products [ 7 , 8 ]. Several species of environmental Myco-bacterium are now known to be of public health importance since they are pathogenic to humans especially those with underlying medical conditions such as being immunocom-promised [ 9 - 11 ]. Rapid detection and identifi-cation of environmental mycobacteria at species level is therefore critical if infections in humans and animals are to be controlled.…”
Section: Introductionmentioning
confidence: 99%